Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I'm attempting to solve a problem involving this differential equation:

$$\frac{dy}{dx} = x^2y^2 + x^2 - y^2 - 1$$

Because this is a separable differential equation, I tend to split the equation between variables $x$ and $y$, and integrate both sites; but I can't seem to get them separated, due to the $x^2y^2$.

$$\frac{dy}{dx} + y^2 = x^2y^2 + x^2 - 1$$ $$ dy + y^2 = x^2y^2\space dx + x^2\space dx - dx$$

Now the only $y$ variable left to get on the opposite side is the $y^2$ that's trapped in $x^2y^2$, but extracting $y^2$ would leave a $y^2$ variable in all the other terms. That's sort of the problem.

$$\frac{dy + y^2}{y^2} = x^2 dx + \frac{x^2}{y^2} dx - \frac{dx}{y^2}$$ $$\frac{dy}{y^2} + 1 = x^2 dx + \frac{x^2}{y^2} dx - \frac{dx}{y^2}$$

And now, if I want the $y$ variables out of the left side, I end up to the previous equation.

$$ dy + y^2 = x^2y^2\space dx + x^2\space dx - dx$$

It's a really bad loop I'm in right now. How can I get around this problem, and get each variable to its seperate side for integration?

share|improve this question
add comment

2 Answers 2

up vote 7 down vote accepted

You can factor the right side as $(y^2+1)(x^2-1)$

share|improve this answer
add comment

Here is a systematic way: assuming your right-hand side, call it $f(x,y) = x^2y^2 + x^2 - y^2 - 1$, actually is separable as $f(x,y) = X(x)Y(y)$, then this will work for any $x_0$ and $y_0$. So arbitrarily choosing $(x_0,y_0) = (0,0)$ for simplicity, we have

$$X(x) \propto \frac{X(x)Y(y_0)}{X(x_0)Y(y_0)} = \frac{f(x,y_0)}{f(x_0,y_0)} = \frac{x^2 - 1}{-1} = 1-x^2.$$

Now with* $X(x)=1-x^2$, we get the other factor

$$Y(y) \propto X(x_0)Y(y) = f(x_0,y) = -y^2 - 1$$

and lo and behold, $X(x) = 1-x^2$ and* $Y(y) = -y^2 - 1$ give $f(x,y)$.

*In taking $X(x) = 1-x^2$, I threw out the constant of proportionality $1/X(x_0)$, and in taking $Y(y) = -y^2 - 1$, I threw out $X(x_0)$. But it's OK since they would have cancelled out anyway. I discovered this shortcut after getting tired of guessing on this type of problem.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.